Distribution and morphological variation of Eleutherodactylus mercedesae Lynch & McDiarmid, 1987 (Amphibia, Anura, Leptodactylidae) with first record for Peru - Padial, José M.; Mcdiarmid, Roy; de La Riva, Igna (Zootaxa, 2006)
We report new distributional information for Eleutherodactylus mercedesae in Bolivia, and provide the first record for Peru based on an adult female. This species, previously endemic to Bolivia, now ranges across about 1000 km in cloud forests on the Amazonian slopes of the Andes from southern Peru to central Bolivia. We provide the first morphological description of females based on two specimens, compare them with the male type and paratype, add some observations to the original description, and comment on variation in the species.